Potensi Pendayagunaan Perantau Buddhis untuk Pembinaan Umat Buddha di Desa Purwodadi Kabupaten Kebumen - Sabar Sukarno (Jurnal Pelita Dharma, 2018)
Villager migrate to cities with the aim of improving themselves in economics and education. Like other communities, many Buddhists in Purwodadi village also migrated. At present, many Buddhist migrants have been able to improve their quality of life by having good livelihoods and successfully taking higher education, spread at several regions in Indonesia. This is a great potential for the development of Buddhists in Purwodadi village.This article aims to describe the potential of Buddhist migrants from Purwodadi village, their contribution to the development of Buddhists in their hometown, and the program for involving Buddhist migrants in future. The data for this article is obtained by observation, interview, and documentation techniques. Interviews were conducted with religious leaders and Buddhists in Purwodadi village.When it was successful, migrants want to contribute to Buddhist development in their hometown. It was found that Buddhist migrants have supported the development of Buddhism, by providing material and non-material assistance. Buddhists in Purwodadi have been benefited from migrants. However, the involvement of migrants is considered not yet optimal, so more efforts are needed to manage Buddhist migrants. Buddhists in Purwodadi village along with Buddhist migrants have developed programs to increase the involvement of Buddhist migrants.Penduduk desa merantau ke kota dengan tujuan meningkatkan diri dalam bidang ekonomi dan pendidikan. Seperti halnya masyarakat lain, banyak umat Buddha di desa Purwodadi juga merantau. Saat ini, banyak perantau Buddhis yang sudah mampu meningkatkan kualitas hidup mereka dengan memiliki mata pencaharian yang baik dan berhasil menempuh pendidikantinggi, tersebar di beberapa daerah di Indonesia. Ini adalah potensi besar bagi pembangunan umat Buddha di desa Purwodadi.Artikel ini bertujuan untuk menggambarkan potensi perantau Buddhis dari desa Purwodadi, kontribusinya bagi pembangunan umat Buddha di daerah asal, dan program untuk meningkatkan keterlibatan perantau Buddhis di masa depan. Data untuk artikel ini diperoleh dengan teknik observasi, wawancara, dan dokumentasi. Wawancara dilakukan dengan para pembina dan umat Buddha di desa Purwodadi.Ketika berhasil, para perantau ingin berkontribusi bagi pembangunan umat Buddha di kampung halaman. Ditemukan bahwa para perantau Buddhis telah mendukung pembangunan umat Buddha, dengan memberikan bantuan materi dan non- materi. Umat Buddha di Purwodadi telah mendapatkan manfaaat dari para perantau. Namun, keterlibatan perantau dianggap belum optimal, sehingga dibutuhkan lebih banyak upaya  untuk mengelola perantau Buddhis. Umat Buddha di desa Purwodadi bersama dengan perantau Buddhis telah mengembangkan program untuk meningkatkan keterlibatan perantau Buddhis.